Method for manufacturing a fast-acting hemostatic cotton medical textile

CN118286494BActive Publication Date: 2026-10-20SHANDONG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410328049.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-21
Publication Date
2026-10-20
Estimated Expiration
2044-03-21

AI Technical Summary

Technical Problem

如刘小军等人对短绒棉进行羧基化改性提升了改性棉的吸水效果,赋予了短绒棉优异的止血性能(柳小军,徐玉茵,刘康博,周静,韩颖,熊玥,田源.羧甲基化棉短绒止血纱布的制备及性能评价[J].中国组织工程研究,2022,26(16):2593-2599.)再比如Yu等人将介孔单晶菱硼沸石紧密结合到棉纤维表面用于快速吸收血液中小分子水分,从而达到血液浓缩的目的,(Yu,L.;Shang,X.;Chen,H.;Xiao,L.;Zhu,Y.;Fan,J.,Atightly-bondedandflexiblemesoporouszeolite-cottonhybridhemostat.NatureCommunications2019,10.)使用无机介孔材料可以激发血小板并牢牢的将其锁在其空腔内,高效的吸血性能使这种材料一直处于是理想的急救品的行列,然而无机介孔材料吸水后会严重膨胀,从而失去其原有的活性并且介孔材料也极易进入血液循环引起血栓形成的潜在风险,从而限制了这类产品的应用空间

Benefits of technology

(1)本发明制备的纳米胶束膜/棉复合材料在制备过程可添加多种止血因子诱导纳米胶束成膜因此产品止血效果更快速、适用范围更广。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118286494B_ABST
    Figure CN118286494B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of cotton textiles, in particular to a preparation method of a quick hemostatic cotton medical textile.A preparation method of a quick hemostatic cotton medical textile, the electrostatic adsorption between the antibacterial cationic polymer and the anionic polymer capable of activating the hemostatic mechanism of platelets self-assembles to form a nanomicelle film and is grafted and compounded with cotton-based materials to finally realize the antibacterial and hemostatic double modification of the cotton medical dressing.The nanomicelle film / cotton composite material prepared by the present application can add various hemostatic factors to induce nanomicelle film formation during the preparation process, so that the product has a faster hemostatic effect and a wider application range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of medical hemostatic materials technology, specifically a method for preparing a rapid hemostatic cotton-based medical textile. Background Technology

[0002] Uncontrollable wound bleeding is a major cause of death among wounded soldiers in modern warfare and a leading cause of death from accidental trauma in peacetime. Cotton fabrics, as materials that can come into direct contact with the human body, have excellent biocompatibility, and as traditional medical dressings, they are highly effective in quickly stopping bleeding from wounds. Currently, cotton hemostatic dressings typically use hemostatic substances to modify the surface of cotton fibers to enhance their hemostatic effect. For example, Liu Xiaojun et al. modified short-staple cotton with carboxylation to improve its water absorption and endow it with excellent hemostatic properties (Liu Xiaojun, Xu Yuyin, Liu Kangbo, Zhou Jing, Han Ying, Xiong Yue, Tian Yuan. Preparation and performance evaluation of carboxymethylated cotton short-staple hemostatic gauze [J]. Chinese Journal of Tissue Engineering Research, 2022, 26(16):2593-2599.). Another example is Yu et al. who tightly bonded mesoporous single-crystal borosilicate to the surface of cotton fibers to rapidly absorb small-molecule water from the blood, thereby achieving blood concentration (Yu, L.; Shang, X.; Chen, H.; Xiao, L.; Zhu, Y.; Fan, J.). (Atightly-bonded and flexible mesoporous zeolite-cotton hybrid hemostat. Nature Communications 2019, 10.) Inorganic mesoporous materials can stimulate platelets and firmly lock them within their cavities. Their highly efficient blood-absorbing properties have made them ideal for emergency treatment. However, inorganic mesoporous materials swell significantly after absorbing water, losing their original activity. Furthermore, they easily enter the bloodstream, posing a potential risk of thrombosis, thus limiting their application. In addition, cotton fabrics that have absorbed blood are highly susceptible to bacterial growth due to the abundant nutrients in the blood, leading to secondary bacterial infections of bleeding wounds. Therefore, cotton textiles used for bleeding wounds must not only have highly efficient hemostatic properties but also the ability to kill bacteria that invade the wound. Summary of the Invention

[0003] To address the aforementioned issues, this invention provides a method for preparing a rapid hemostatic cotton-based medical textile. The electrostatic adsorption between an antibacterial cationic polymer and an anionic polymer that can activate platelet hemostasis mechanisms leads to the self-assembly of a nano-micelle membrane, which is then grafted onto a cotton-based material to ultimately achieve dual antibacterial and hemostatic modification of the cotton-based medical dressing.

[0004] The technical solution adopted by this invention to solve its technical problem is: a method for preparing a rapid hemostatic cotton-based medical textile, comprising the following steps: S1. Preparation of nanomicelle solution C: Prepare an aqueous solution A of 2% by mass of modified cationic polymer M-PHGC and an aqueous solution B of 1% by mass of anionic polymer carboxymethyl cellulose sodium. Take 50-200 mL of solution A and 50-200 mL of solution B respectively and mix them. Stir for 1-10 min until the formed micelle particles are dispersed and stabilized to prepare nanomicelle solution C. After system C is stable, let it stand at low temperature for later use. The concentrations of aqueous solutions A and B are both 0.5%-4%, and the mixing ratio is between 1:5 and 5:1. S2. Free radical initiation finishing of cotton fabrics: Cotton fabrics are treated with an initiator under appropriate conditions to create free radicals on the surface of the cotton fabrics that can initiate the polymerization of unsaturated double bonds. S3. Surface treatment of cotton fabric: By controlling the charge and dispersion concentration on the surface of the nano micelle particles, an electrolyte solution and nano micelle particles are added. The charge carried by the electrolyte solution and the nano micelle particles induces the aggregation and precipitation of the micelle particles, and finally a layer of nano micelle particle coating is deposited on the surface of the cotton fabric. Free radical grafting copolymerization reaction occurs between the nano micelle particles containing double bonds and between the micelle particles with double bonds and the cotton fabric containing free radicals on the surface.

[0005] The cationic and anionic polymers used must contain one or both of the double bonds that can be polymerized by free radicals in order to facilitate the subsequent grafting modification of cotton fabrics.

[0006] As an optimization, the preparation process of the modified cationic polymer M-PHGC aqueous solution A is as follows: Dissolve 5-10g of cationic polymer in 20-100mL of dimethyl sulfoxide solution, adjust the pH to 8-10 by adding triethylamine solvent, then add double bond modifier, react at room temperature for 12-24h, and after the reaction is completed, use acetone or dichloromethane as precipitant, filter and purify, and dry in a vacuum drying oven at room temperature to prepare free radical polymerizable double bond modified cationic macromonomer M-PHGC.

[0007] As an optimization, the cationic polymer is one of polyhexamethylene guanidine hydrochloride, double bond modified polyhexamethylene guanidine hydrochloride M-PHGC, polyhexamethylene guanidine biguanide hydrochloride, and polymethacryloyloxyethyltrimethylammonium chloride, wherein the molecular chain of the cationic polymer contains -NH2 end functional groups. The double bond modifier is a monomer with reactive double bonds that can undergo affinity substitution reactions with primary amine functional groups, including one of methacrylic anhydride, maleic anhydride, and glycidyl methacrylate, and the amount added is 10-50% of the cationic polymer mass.

[0008] As an optimization, the preparation process of the anionic polymer sodium carboxymethyl cellulose aqueous solution B is as follows: 1-2g of anionic polymer was dissolved in 100-200mL of deionized water, and 20-100mL of double bond modifier was slowly added dropwise. Under ice bath stirring conditions, the pH value was adjusted to 8-10 using 0.01-0.1mol / L sodium hydroxide solution, and the reaction was continued for 12-24h. After the reaction was completed, ethanol was used for precipitation, and the monomer M-CMC, which is a free radical polymerizable anionic polymer, was prepared by drying in a vacuum drying oven at room temperature.

[0009] During the reaction, a co-solvent can be added to increase the solubility of the double bond modifier in the solution. The co-solvent is a non-protic solvent with good water solubility, such as acetone, dioxane, or N'N-dimethylacetamide, and the amount used is 5%-20% of the final solution volume.

[0010] As an optimization, the degree of substitution of the anionic polymer is between 0.2 and 0.8, and the molecular weight is between 80,000 and 100,000. The anionic polymer is one of anionic polymers such as sodium carboxymethyl cellulose, double bond modified sodium carboxymethyl cellulose M-CMC, and polyacrylic acid. The double bond modifier is one of methacrylic anhydride, acrylic anhydride, maleic anhydride, and acryloyl chloride, and the amount of the double bond modifier added is 20-60 mL.

[0011] As an optimization, the specific steps of free radical initiation finishing of cotton fabric in step S2 are as follows: Soak 10-50g of cotton fabric in deionized water at a bath ratio of 1:20-1:50, add 1-10g of initiator A, heat to 60-80°C, and treat with nitrogen gas for 30-120 minutes. Remove the cotton fabric and rinse it with deionized water 1-3 times for later use.

[0012] As an optimization, the initiator A includes one or more of the following: cerium ammonium nitrate, ammonium persulfate, potassium persulfate, a compound system of ammonium persulfate and sodium sulfite, a compound system of ferrous ions and potassium persulfate, and a compound system of ferrous ions and hydrogen peroxide.

[0013] Free radicals on the surface of cotton fabrics can initiate the graft copolymerization of nanomicelle particles with double bonds on the surface of cotton fabrics. Moreover, free radicals on the surface of cotton fabrics can also initiate the polymerization of unsaturated double bonds between nanomicelle particles after chain transfer. However, during the chain transfer process, free radicals may disproportionate and terminate, resulting in some double bonds between nanomicelle particles not being fully polymerized. To avoid this situation, an initiator B needs to be added to initiate the double bond reaction between nanomicelle particles.

[0014] As an optimization, the specific steps for surface treatment of cotton fabric in step S3 are as follows: 10-15g of the cotton fabric obtained in step S2 is spread evenly in a 1000mL beaker. 100-500mL of the micelle solution C prepared in step S1 and 2-10g of initiator B are added. 10-50mL of electrolyte solution is added dropwise. The temperature is raised to 40-80℃ and then allowed to stand for 6-12h to complete the sedimentation of nano micelle particles on the surface of the cotton fabric. After the reaction is completed, the cotton fabric is rinsed with deionized water and dried to obtain the final product. The electrolyte solution includes one of FeCl3 solution, CaSO4 solution, AlCl3 solution, negatively charged styrene emulsion, and polysiloxane emulsion, and the concentration of the electrolyte solution is 0.5%-2%.

[0015] Double bond grafting polymerization of nanomicelle particles involves free radical grafting copolymerization reactions between nanomicelle particles containing double bonds and between nanomicelle particles with double bonds and cotton fabrics containing free radicals on their surface. This achieves the permanent fixation of the nanomicelle film on the surface of cotton fabrics, thereby enhancing the wash resistance of cotton fabrics after functional finishing.

[0016] In addition to neutralizing the surface charge of micelles, heating and stirring can also accelerate the aggregation and sedimentation of micelle particles. Therefore, in the sedimentation process of nano micelle particles on the surface of cotton fabric, the sedimentation process can be accelerated by heating and stirring in the early stage. The heating and stirring time can be controlled between 30-120 minutes.

[0017] As an optimization, the initiator B includes an aqueous free radical initiator or a redox reaction two-component complex; The aqueous free radical initiator includes one of potassium persulfate, ammonium persulfate, and hydrogen peroxide; the redox reaction binary complex includes one of the following systems: potassium persulfate and ferrous ions, hydrogen peroxide and ferrous ions, and ammonium persulfate and sodium bisulfite.

[0018] This solution provides a method for preparing a rapid hemostatic cotton-based medical textile, which has the following advantages: (1) The nano micelle film / cotton composite material prepared by the present invention can be added with a variety of hemostatic factors to induce nano micelle film formation during the preparation process, so the product has a faster hemostatic effect and a wider range of applications.

[0019] (2) The present invention has a novel nanomicelle preparation process, controllable reaction conditions, low energy consumption, and more importantly, it adopts covalent grafting modification. The strong binding between the nanomicelle particles and cotton fabric can ensure that they will not enter the blood and cause the risk of thrombosis.

[0020] (3) No toxic solvents are used in the process of this invention, so it is harmless to the environment. The solvent can be recycled, the cost is low, and the product has no toxic effects on the human body. Attached Figure Description

[0021] Figure 1 This is a schematic diagram illustrating the self-assembly principle of nanomicelles in Example 1 of the present invention; Figure 2 This is a schematic diagram illustrating the aggregation and dispersion effects of nanomicelles in Example 1 of the present invention; Figure 3 This is an electron micrograph of nanomicelles deposited on the surface of cotton fabric prepared by the method in Example 1 of this invention; Figure 4 This is a diagram showing the antibacterial zone effect of the modified cotton fabric obtained in Example 1 of the present invention. Figure 5 This is a visual representation of the nanomicelle composite cotton fabric obtained in Example 1 of the present invention. Figure 6 This is a diagram illustrating the in vitro hemostatic effect of the composite cotton fabric in Embodiment 3 of the present invention. in, Figure 3 and Figure 4 In this application, A refers to the fast-acting hemostatic cotton medical textile, and B refers to ordinary pure cotton fabric. Figure 5 The micelle composite fabric mentioned in this application is the rapid hemostatic cotton medical textile.

[0022] Figure 6 Figure A shows the hemostatic effect of the rapid hemostatic cotton medical textile of this application, and Figure B shows the external hemostatic effect of ordinary cotton fabric. The more filter paper in the figure, the longer the bleeding time of the wound. Detailed Implementation

[0023] Example 1 (1) Dissolve 1g of sodium carboxymethyl cellulose in 100mL of deionized water. After it is fully dissolved, add 20mL of methacrylic anhydride and 10mL of dioxane co-solvent. Stir for 10min and then add 5mL of 0.1mol / L NaOH solution. React for 24h under ice bath conditions in the dark. The product obtained by using anhydrous ethanol as a precipitant is filtered and purified. Then, it is dried in a vacuum drying oven at room temperature to obtain sodium carboxymethyl cellulose (M-CMC), a modified anionic polymer containing double bonds.

[0024] The double bond modifier is one of methacrylic anhydride, acrylic anhydride, maleic anhydride, and acryloyl chloride, and the amount of the double bond modifier added is 20-60 mL.

[0025] During the reaction, a co-solvent can be added to increase the solubility of the double bond modifier in the solution. The co-solvent is a non-protic solvent with good water solubility, such as acetone, dioxane, or N'N-dimethylacetamide, and the amount used is 5%-20% of the final solution volume.

[0026] (2) Dissolve 2g of commercially available polyhexamethylene guanidine hydrochloride (PHGC) in 1000mL of deionized water to obtain a cationic polymer solution SQ; dissolve 2g of double-bond modified sodium carboxymethyl cellulose in 1000mL of deionized water to prepare a modified anionic polymer solution SN. Slowly add 150mL of SQ solution to 150mL of SN solution and gently shake to obtain a nanomicelle dispersion.

[0027] The double bond modifier is a monomer with reactive double bonds that can undergo affinity substitution reactions with primary amine functional groups, including one of methacrylic anhydride, maleic anhydride, and glycidyl methacrylate, and the amount added is 10-50% of the cationic polymer mass.

[0028] (3) Place 10g of cotton cloth in 300mL of deionized water, add 2g of cerium ammonium nitrate, heat to 70℃ with nitrogen gas and react for 30min. Take out the cotton cloth and wash it three times with deionized water. Then put the cotton cloth into the nano micelle dispersion in step 2, add 4mL of dimethyl silicone oil to accelerate the coagulation of the nano micelle solution, and slowly raise the temperature to 60℃ after 20min to deposit a layer of nano micelle film on the surface of the cotton cloth.

[0029] The electrolyte solution used includes one of FeCl3 solution, CaSO4 solution, AlCl3 solution, negatively charged styrene emulsion, polysiloxane emulsion, and dimethyl silicone oil, and the concentration of the electrolyte solution is 0.5%-2%.

[0030] The initiator A used includes one or more of the following: cerium ammonium nitrate, ammonium persulfate, potassium persulfate, a compound system of ammonium persulfate and sodium sulfite, a compound system of ferrous ions and potassium persulfate, and a compound system of ferrous ions and hydrogen peroxide.

[0031] (4) After the nano micelles in step (3) have completely precipitated, add 100 mg of potassium persulfate to the solution system and slowly add 10 mL of aqueous solution containing 100 mg of sodium bisulfite. After reacting for 1 hour, take out the cotton cloth and let it air dry naturally at room temperature.

[0032] Initiator B used includes aqueous free radical initiators or redox reaction two-component complexes; The aqueous free radical initiator includes one of potassium persulfate, ammonium persulfate, and hydrogen peroxide; the redox reaction binary complex includes one of the following systems: potassium persulfate and ferrous ions, hydrogen peroxide and ferrous ions, and ammonium persulfate and sodium bisulfite.

[0033] Among them, nanomicelles are self-assembled from anionic and cationic polymers through electrostatic adsorption. The assembly principle is as follows: Figure 1As shown. Under low concentration conditions, the nanomicelles can be well dispersed in water. However, after adding certain flocculants (dimethyl silicone oil was added in Example 1), the surface charge of the nanomicelle particles is neutralized, and the nanomicelle particles begin to aggregate and settle. The settling process is as follows. Figure 2 As shown.

[0034] After cotton fabric is treated with cerium ammonium nitrate, free radicals that can initiate double bond polymerization are introduced onto its surface. The cotton fabric is then placed in a nanomicelle solution, and a coagulant is added to accelerate its aggregation and sedimentation. Once the nanomicelles have aggregated on the surface of the cotton fabric to form a nanomicelle film (observed by electron microscopy)... Figure 3 A distinct membrane structure composed of nanomicelles can be observed. Free radicals on the surface of the cotton fabric can initiate the polymerization of double bonds on the modified anionic polymer (M-CMC) in the nanomicelle particles, thereby achieving the grafting modification of the cotton fabric and the surface nanomicelles. In order to ensure the double bond copolymerization between all the modified anionic polymers in the nanomicelle film, after the nanomicelles have completed the coagulation on the surface of the cotton fabric, potassium persulfate and sodium bisulfite are added to continue the initiation at room temperature until the double bond reaction is complete.

[0035] Because only the anionic polymers in the nanomicelle particles have double bonds and are ultimately polymerized through initiation, while the cationic polymers and anionic polymers remain bound by electrostatic adsorption, the cationic polymers can be slowly released during the sterilization process for continuous sterilization. Therefore, the resulting composite cotton fabric was tested for antibacterial activity according to the international standard AATCC-90. The results showed that the cotton fabric composited with nanomicelle particles exhibited an antibacterial ring with a radius of up to 2 mm. Figure 4 As shown. Furthermore, the thickness of the nanomicelle film can be controlled by the number of times or the volume of nanomicelles settling on the cotton fabric surface. Figure 5 Small amounts of deposited nanomicelle particles have little impact on the appearance of cotton fabrics, but large amounts of deposited nanomicelle particles will form a transparent film on the surface of cotton fabrics. This film will affect the feel of the cotton fabrics, making them rough and stiff.

[0036] Example 2 (1) Dissolve 1g of sodium carboxymethyl cellulose in 100mL of deionized water. After it is fully dissolved, add 20mL of methacrylic anhydride and 10mL of dioxane co-solvent. Stir for 10min and then add 5mL of 0.1mol / L NaOH solution. React for 24h under ice bath conditions in the dark. The product obtained by using anhydrous ethanol as a precipitant is filtered and purified. Then, it is dried in a vacuum drying oven at room temperature to obtain sodium carboxymethyl cellulose (M-CMC), a modified anionic polymer containing double bonds.

[0037] (2) Dissolve 5g of commercially available polyhexamethylene guanidine hydrochloride (PHGC) in 20mL of dimethyl sulfoxide solution, add 5mL of methacrylic anhydride, add 3mL of triethylamine solution, react at room temperature in the dark for 24h, then precipitate with dichloromethane, filter and dry at room temperature to obtain double bond modified M-PHGC.

[0038] Dissolve 2g of M-PHGC in 1000mL of deionized water to obtain cationic polymer solution SQ1; dissolve 2g of double-bond modified sodium carboxymethyl cellulose in 1000mL of deionized water to prepare modified anionic polymer solution SN1. Slowly add 150mL of SQ1 solution to 150mL of SN1 solution and gently shake to obtain a nanomicelle dispersion.

[0039] (3) Place 10g of cotton cloth in 300mL of deionized water, add 2g of cerium ammonium nitrate, heat to 70℃ with nitrogen gas and react for 30min. Take out the cotton cloth and wash it three times with deionized water. Then put the cotton cloth into the nano micelle dispersion in step 2, add 4mL of dimethyl silicone oil to accelerate the coagulation of the nano micelle solution, and slowly raise the temperature to 60℃ after 20min to deposit a layer of nano micelle film on the surface of the cotton cloth.

[0040] (4) After the nanomicelles in step (3) have completely precipitated, add 100 mg of ammonium persulfate to the solution system and slowly add 10 mL of an aqueous solution containing 100 mg of sodium bisulfite. After reacting for 1 hour, remove the cotton fabric and let it air dry naturally at room temperature. According to the AATCC-100 standard, the antibacterial effect of the obtained cotton fabric against Staphylococcus aureus and Klebsiella pneumoniae is above 99%.

[0041] Example 3 (1) Dissolve 8g of commercially available polyhexamethylene guanidine hydrochloride (PHGC) in 20mL of dimethyl sulfoxide solution, add 5mL of methacrylic anhydride, and dropwise add 3mL of triethylamine solution. React at room temperature in the dark for 24h, then precipitate with dichloromethane, filter, and dry at room temperature to obtain double bond modified M-PHGC. Dissolve 2g of M-PHGC in 1000mL of deionized water to obtain cationic polymer solution SQ2; dissolve 2g of sodium carboxymethyl cellulose in 1000mL of deionized water to prepare modified anionic polymer solution SN2. Slowly add 150mL of SQ2 solution to 150mL of SN2 solution and gently shake to obtain a nanomicelle dispersion.

[0042] (2) Place 30g of cotton cloth in 300mL of deionized water, add 2g of cerium ammonium nitrate, heat to 70℃ with nitrogen gas and react for 30min. Take out the cotton cloth and wash it three times with deionized water. Then put the cotton cloth into the nano micelle dispersion in step 2, add 4mL of 0.01mol / L FeCl3 solution to accelerate the coagulation of the nano micelle solution. After 20min, slowly raise the temperature to 60℃ to deposit a layer of nano micelle film on the surface of the cotton cloth.

[0043] (3) After the nanomicelles in step (3) have completely precipitated, add 100 mg of potassium persulfate to the solution system and slowly add 10 mL of an aqueous solution containing 100 mg of sodium bisulfite. After reacting for 1 hour, remove the cotton fabric and let it air dry naturally at room temperature. According to the AATCC-100 standard, the antibacterial effect of the obtained cotton fabric against Staphylococcus aureus and Klebsiella pneumoniae is above 99%.

[0044] Because the carboxylate group on the sodium carboxymethyl cellulose macromolecule chain can activate the platelet hemostasis mechanism; the guanidinium group on the cationic polymer (PHGC) can adsorb and aggregate negatively charged platelets to accelerate hemostasis; and in addition, the use of Ca 2+ As a hemostatic factor, the coagulant can induce fibrin in the blood to cross-link into a network, thereby blocking the wound. Therefore, the resulting nano-micelle composite cotton fabric has excellent hemostatic effect. To verify this, the product obtained in Example 3 was subjected to an in vitro hemostatic experiment, and the results are as follows: Figure 6 The final product shown has a significantly shorter hemostasis time compared to ordinary cotton fabric products.

[0045] Example 4 (1) Dissolve 2g of sodium carboxymethyl cellulose in 100mL of deionized water. After it is fully dissolved, add 20mL of methacrylic anhydride and 10mL of dioxane co-solvent. Stir for 10min and then add 5mL of 0.1mol / L NaOH solution. React for 24h under ice bath conditions in the dark. The product obtained by using anhydrous ethanol as a precipitant is filtered and purified. Then, it is dried in a vacuum drying oven at room temperature to obtain sodium carboxymethyl cellulose (M-CMC), a modified anionic polymer containing double bonds.

[0046] (2) Dissolve 10g of commercially available polyhexamethylene guanidine biguanide (PHMG) in 1000mL of deionized water to obtain cationic polymer solution SQ3; dissolve 2g of double-bond modified sodium carboxymethyl cellulose in 1000mL of deionized water to prepare modified anionic polymer solution SN3. Slowly add 150mL of SQ3 solution to 150mL of SN4 solution and gently shake to obtain nanomicelle dispersion.

[0047] (3) Place 50g of cotton cloth in 300mL of deionized water, add 150mg of ammonium persulfate and 120mg of sodium bisulfite, react at room temperature for 30min, take out the cotton cloth and wash it three times with deionized water, then put the cotton cloth into the nano micelle dispersion in step 2, add 4mL of dimethyl silicone oil to accelerate the coagulation of the nano micelle solution, and after 20min, slowly raise the temperature to 60℃ to deposit a layer of nano micelle film on the surface of the cotton cloth.

[0048] (4) After the nanomicelles in step (3) have completely precipitated, add 100 mg of potassium persulfate to the solution system and heat to 60 °C. After reacting for 1 h, remove the cotton fabric and let it air dry naturally at room temperature. According to the AATCC-100 standard, the antibacterial effect of the obtained cotton fabric against Staphylococcus aureus and Klebsiella pneumoniae is above 99%.

[0049] The above-described specific embodiments are merely specific examples of the present invention. The patent protection scope of the present invention includes, but is not limited to, the product form and style of the above-described specific embodiments. Any method for preparing a fast hemostatic cotton medical textile that conforms to the claims of the present invention, and any appropriate changes or modifications made thereto by those skilled in the art, shall fall within the patent protection scope of the present invention.

Claims

1. A method for preparing a rapid hemostatic cotton-based medical textile, characterized in that: Includes the following steps: S1. Preparation of nanomicelle solution C: Prepare an aqueous solution A of 2% (w / w) modified cationic polymer M-PHGC and an aqueous solution B of 1% (w / w) anionic polymer carboxymethyl cellulose sodium. Take 50-200 mL of solution A and 50-200 mL of solution B respectively, mix them, and stir for 1-10 min until the formed micelle particles are dispersed and stable to obtain nanomicelle solution C. After system C is stable, let it stand at low temperature for later use. The concentrations of aqueous solutions A and B are both 0.5%-4%, and the mixing ratio is between 1:5 and 5:

1. S2. Free radical initiation finishing of cotton fabrics: Cotton fabrics are treated with initiator A under appropriate conditions to create free radicals on the surface of the cotton fabrics that can initiate the polymerization of unsaturated double bonds. S3. Surface treatment of cotton fabric: 10-15g of the cotton fabric obtained in step S2 is spread evenly in a 1000mL beaker. 100-500mL of the micelle solution C prepared in step S1 and 2-10g of initiator B are added. 10-50mL of electrolyte solution or dimethyl silicone oil is added dropwise. The temperature is raised to 40-80℃ and then allowed to stand for 6-12h to complete the deposition of nano-micelle particles on the surface of the cotton fabric. After the reaction is complete, the cotton fabric is rinsed with deionized water and dried to obtain the final product. The electrolyte solution includes FeCl3 solution, and the concentration of the electrolyte solution is 0.5%-2%. By controlling the charge and dispersion concentration on the surface of the nano-micelle particles, adding electrolyte solution and nano-micelle particles, the charge carried by the electrolyte solution and nano-micelle particles induces the aggregation and precipitation of the micelle particles, ultimately depositing a layer of nano-micelle particle coating on the surface of the cotton fabric. Free radical grafting copolymerization reactions occur between nano-micelle particles containing double bonds and between micelle particles with double bonds and cotton fabric containing free radicals on the surface. The preparation process of the modified cationic polymer M-PHGC aqueous solution A is as follows: Dissolve 5-10g of cationic polymer PHGC in 20-100mL of dimethyl sulfoxide solution, adjust the pH to 8-10 by adding triethylamine solvent, then add a double bond modifier, and react at room temperature for 12-24h. After the reaction, use acetone or dichloromethane as a precipitant, filter and purify, and dry in a vacuum drying oven at room temperature to prepare free radical polymerizable double bond modified cationic macromonomer M-PHGC. The double bond modifier used to prepare M-PHGC is a monomer with reactive double bonds that can undergo affinity substitution reaction with primary amine functional groups, including methacrylic anhydride, and the amount added is 10-50% of the cationic polymer mass. The preparation process of the anionic polymer sodium carboxymethyl cellulose aqueous solution B is as follows: 1-2g of sodium carboxymethyl cellulose anionic polymer was dissolved in 100-200mL of deionized water. 20-100mL of double bond modifier was slowly added dropwise. Under ice bath stirring, the pH was adjusted to 8-10 using 0.01-0.1mol / L sodium hydroxide solution. The reaction was continued for 12-24h. After the reaction, ethanol was used for precipitation, and the mixture was dried in a vacuum drying oven at room temperature to prepare the free radical polymerizable anionic polymer monomer M-CMC. The double bond modifier used to prepare M-CMC was methacrylic anhydride, and the amount added was 20-60mL. The initiator A includes cerium ammonium nitrate.

2. The method for preparing a rapid hemostatic cotton-based medical textile according to claim 1, characterized in that: In step S2, the specific steps for free radical initiation finishing of cotton fabric are as follows: Soak 10-50g of cotton fabric in deionized water at a bath ratio of 1:20-1:50, add 1-10g of initiator A, heat to 60-80°C, and treat with nitrogen gas for 30-120 minutes. Remove the cotton fabric and rinse it with deionized water 1-3 times for later use.

3. The method for preparing a rapid hemostatic cotton-based medical textile according to claim 2, characterized in that: The initiator B includes an aqueous free radical initiator or a redox reaction two-component complex; The aqueous free radical initiator includes one of potassium persulfate and ammonium persulfate; the redox reaction binary complex includes an ammonium persulfate and sodium bisulfite system.

Citation Information

Patent Citations

  • Preparation method of styptic powder

    CN114522270A

  • Preparation method of electronegative micromolecule regulated cationic polymer-based hemostatic material

    CN115350319A